Characterization of PM2.5 and conversion rate of sulfur dioxide to sulfate in inland areas of Taiwan. Issue 3 (12th March 2008) - Horng, Chuen-Liang; Cheng, Man-Ting
Abstract : The purpose of this study was to investigate the sulfur conversion rate and the characterization of PM2.5 particulate matter and acidic gases in inland Taiwan region. The measurements were taken at two different sites located near the fossil fuel power plant in central Taiwan. First site was Wufong and the other site was Nantou, which is located 15 km south from Wufong. PM2.5 and gaseous acids were measured by annular denuder system. PM2.5 ionic species including SO4 2–, NO3 –, NH4 +, Cl –, Ca 2+, K +, Na +, and H + and gaseous HNO3 and HCl were analyzed. Results showed that the average ratio of PM2.5 and SO4 2– was higher during daytime, probably due to the anthropogenic activities. Wind field map also clearly displayed that Wufong was located upwind and Nantou was located downwind during daytime. Sulfur conversion ratio in the downwind site was higher than upwind site. Experimental data showed that sulfur conversion rate between these sites was 5%–9% h –1 . The increased PM2.5 and SO2 concentrations recorded in the Nantou site were from the direction of Taichung city during daytime.